City Branding Kota Bandung Sebagai Kota Berpotensi Melalui Program Sister City - Nindy Metha Mayangswari; Yudha Mardhatillah (Program Studi Teknologi Rekayasa Informasi Pemerintahan, 2022)
Bandung has several sister city program, but the sister city program with Suwon City is the most successful by the Government of Bandung. But in fact, the sister city program Bandung Suwon-City did not go well. This study is done to find out why (the reason) Bandung conduct a sister city program with Suwon. This study is a qualitative research with paradigm of constructivism and using study case method. The data collection is done by observations, interviews, and literature reviews. The results of this study is that there are some commonalities which underlie the establishment of the sister city program. They are the friendships between the two mayors who served the cities, the similarity of geographic, demographic, education and culture, also the same vision and mission of both cities.